Parametric sweep simulation for greenhouse temperature field optimization: An Italian case study. (November 2022) - Morelli, Stefano; Cossio, Filippo; Monarca, Danilo; Marucci, Alvaro; Selli, Sara; Pierini, Daniele; Carlini, Maurizio
Abstract: The increasing importance of protected cultures in the last decades has led to the definition of aims for greenhouse design and functioning, in order to conjugate productivity and environmental sustainability. In particular, the optimization of greenhouses is finalized to better solar radiation adsorption and ensure to the crops a homogeneous temperature field for the whole growth time. An Italian case study is presented in this paper: the studied farm needs to project greenhouse geometry and design a hot-water pipes heating system to cultivate basil during the winter season, improving the exploitation of natural resources. A simulative analysis has been carried out by mean of COMSOL Multiphysics software, investigating the effects of greenhouse height, number of pipes and water temperature of the heating system on the inside temperature field through a parametric sweep approach. Twenty-seven scenarios have been simulated and three of them have been considered suitable for the farm applications. The simulative approach allows to collect data about the minimum number of pipes, the sensitivity of the internal temperature field to the outside temperature fluctuation (referred also to the height of the greenhouse) and the more suitable heating water temperature needed to ensure the required habitat to the basil crops, minimizing also temperature fluctuations.